Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1097/01.sla.0000256392.04141.04
|View full text |Cite
|
Sign up to set email alerts
|

A State-wide Review of Contemporary Outcomes of Gastric Bypass in Florida

Abstract: Increased utilization of bariatric surgery in Florida is associated with overall favorable short-term outcomes. Older age and male gender were associated with increased morbidity and mortality. Surgeon and hospital procedure volume have an inverse relationship with in-hospital complications and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
1
20
0
4
Order By: Relevance
“…All six studies 27,28,30,36,38,39 examining surgical sequelae demonstrated increases in complications with lower surgeon volumes, including the three studies that reported adjusted results (Table 3).…”
Section: Association Between Facility-level or Surgeonlevel Surgmentioning
confidence: 99%
See 2 more Smart Citations
“…All six studies 27,28,30,36,38,39 examining surgical sequelae demonstrated increases in complications with lower surgeon volumes, including the three studies that reported adjusted results (Table 3).…”
Section: Association Between Facility-level or Surgeonlevel Surgmentioning
confidence: 99%
“…Hospital Volume. All seven studies 26,27,[30][31][32]34,35 examining mortality found a significant inverse association between surgical volume and mortality ( (Table 3). One study 27 (n = 19,174) reported significantly higher mortality for surgeons who performed < 99 cases versus ≥ 500 cases over five years (RR 2.85, 95% CI, 1.32-6.16).…”
Section: Association Between Facility-level or Surgeonlevel Surgmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] As a result, the number of bariatric surgical procedures has also increased [2][3][4]. The implications for anesthetic and perioperative care of severely obese patients are considerable, and are believed to escalate in the presence of co-morbidities [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos 15 años, hemos logrado establecer un programa de tratamiento quirúrgico de la obesidad, con excelentes resultados a largo plazo, con una tasa de complicaciones comparables con las grandes series publicadas en la literatura mundial [29][30][31][32][33][34][35] . En nuestra experiencia, la mortalidad global postoperatoria es de 0,04%.…”
Section: Discussionunclassified